Preclinical safety assessments of nano‐sized constructs on cardiovascular system toxicity: A case for telemetry. Issue 11 (6th February 2017) - Cheah, Hoay Yan; Kiew, Lik Voon; Lee, Hong Boon; Japundžić‐Žigon, Nina; Vicent, Marίa J.; Hoe, See Ziau; Chung, Lip Yong
Abstract: While nano‐sized construct (NSC) use in medicine has grown significantly in recent years, reported unwanted side effects have raised safety concerns. However, the toxicity of NSCs to the cardiovascular system (CVS) and the relative merits of the associated evaluation methods have not been thoroughly studied. This review discusses the toxicological profiles of selected NSCs and provides an overview of the assessment methods, including in silico, in vitro, ex vivo and in vivo models and how they are related to CVS toxicity. We conclude the review by outlining the merits of telemetry coupled with spectral analysis, baroreceptor reflex sensitivity analysis and echocardiography as an appropriate integrated strategy for the assessment of the acute and chronic impact of NSCs on the CVS. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : While nano‐sized construct (NSC) use in medicine has grown significantly in recent years, reported unwanted side effects have raised safety concerns. However, toxicity of NSCs to the cardiovascular system and relative merits of the associated evaluation methods have not been thoroughly studied. This review discusses the toxicological profiles of selected NSCs and provides an overview of the assessment methods, including in silico, in vitro, ex vivo and in vivo models and how they are related to cardiovascular system toxicity.